Eco-touristic strategy to Visualize the culture of Colombian indigenous communities: case Putumayo - Mosquera Laverde, William Eduardo; Plata Rincón, Leydi Juliet; González Cortés, Ángela Milena (Cooperativismo & Desarrollo, 2021)
The article presents a management proposal in marketing ecotourism projects in indigenous communities of Putumayo - Colombia, focusing on the design of a strategy to make the potential tourist sites and cultural aspects visible to allow a better territorial development in the natural areas studied; through this, it is intended to generate a considerable impact on the socio-cultural and economic development in the department of Putumayo. It begins with the characterization of the indigenous communities of the municipality of Orito, from the geographic, demographic, spatial, cultural, political and organizational dimensions, then, the communities with greater potential to implement ecotourism activities are determined, identifying the ecotourism attractions in their territories. Finally, the market strategy is based on the project management guides: WWF and PMBOK, from which the components were extracted to design the visibility strategy to improve the marketing management of the communities, as an adaptive and simple tool for the management of ecotourism projects in ethnic communities so far away from State support and that allows them to preserve their cultural identity.